Exploring the influence of cultural and health beliefs on intentions to adopt COVID-19 prevention measures - Dam, L.; Basaran, A.-M.B.; Lin, C.A.; Rogers, D. (Atlantic Journal of Communication, 2022)
This study explores how individuals react to COVID-19 prevention measures in relation to their national cultural values and health belief factors. Specifically, guided by the most relevant Hofstede’s cultural dimensions and the health belief model (HBM), this study tested a conceptual framework through conducting a survey of the U.S. adult population. The study results did not support Hofstede’s classification of the U.S. to be among the most individualistic culture with the lowest level of uncertainty avoidance in the world. Demographic factors such as ethnicity, gender, age, and education were found to be significantly related to collectivistic tendency and/or uncertainty avoidance. Findings also demonstrated that the tendency for collectivism and uncertainty avoidance were both relevant to people’s intention to adopt COVID-19 prevention measures. Results of testing the HBM variables revealed that perceived barriers, perceived self-efficacy, and cues to action were significantly related to preventive behavioral intentions. This study highlights the importance of considering subculture factors when promoting COVID-19 preventive measures in a multicultural society. © 2022 Atlantic Journal of Communication.
1 citations (Crossref) [2023-10-31] tex.document_type: Article tex.source: Scopus
Keywords: dept.com; peer-reviewed